-6.5=-1.3x

Simple and best practice solution for -6.5=-1.3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6.5=-1.3x equation:


-6.5=-1.3x

We simplify the equation to the form, which is simple to understand
-6.5=-1.3x

We move all terms containing x to the left and all other terms to the right.
+1.3x=+6.5

We simplify left and right side of the equation.
+1.3x=+6.5

We divide both sides of the equation by 01.3 to get x.
x=5

See similar equations:

| ln(3x)+ln(2x)=3 | | -7x=1-(-6) | | 3(5.33+6)= | | 5v-(-27)=97 | | 56x^2y-21xy^2= | | m^3+5m^3-9m-45=0 | | 2x^2+2y^2=72 | | 2x^2=4-2x | | 4x-5=-5+7x | | -52+-26a=208 | | 22-2t=8 | | b=512 | | 3(5.33+6)+15(5.33)= | | (6-x)+(7-x)-(4-x)=0 | | 18=-12(7x-2) | | 3.98(x-15)-2.20x=107.62 | | 4x^3-2x+2=0 | | 10-7(6-5x)=4(6-x)-10x | | 3.98(x-15)-2.20=107.62 | | 3(n+6)+15n=114 | | -7-5=-2+x | | 2+2s=4 | | 16=5-5x | | 36x+67=468 | | 4+2z=20 | | 35*5+.10m=25.5+.25m | | 36x+67= | | 3(n+6)+15n= | | 72n^4-120n^2+50=0 | | 10-4p+28=2-2p | | 9t-6-6t=g | | 2=10-2g |

Equations solver categories